Consumer behaviour in the bottom level of Pyramid markets with reference to Urban segments (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The ‘bottom of the pyramid’ approach, by C. K Prahalad, proposed that ‘marketing to the poor in increasing countries is the best way to instantaneously progress emergent economies and business profits’ (Prahalad, 2004). Firms are ideally well positioned to seek the fortune at the bottom of the pyramid due to their compensations in both scale and scope. As recent research in this area argues, the rural bottom of the pyramid (BOP) is dispersed, distant, extremely poor, heterogeneous and mostly illiterate. Operating in this segment is also physically, economically, and politically risky. A more realistic and sustainable alternative is to target the urban BOP.  Although research in this area is relatively new, most of the work done is towards the supply side of the problem. The research done so far has largely remained silent on the demand or the consumption side of the BOP. The thesis elaborately explores the consumer or demand side of the Bottom of the Pyramid concept specifically focusing on the urban BOP. This importance of this study is twofold; firstly, it takes a more realistic approach towards the BOP by eliminating the dynamic barriers of the rural BOP. This will encourage broader business engagement. Secondly, this is one of the first few empirical studies that has been conducted with the motivation to understand the consumer behaviour of the urban BOP market especially with an Indian context.